Narrazioni virali. Decostruire (e ricostruire) il racconto dell’emergenza coronavirus - Pedroni, Marco (Mediascapes journal, 2020)
This essay analyses the first phase of the coronavirus emergency in Italy, known as "Phase 1" (from the end of February to the beginning of May 2020) by identifying three dominant narratives (epidemiological, domestic, utopian) that have marked respectively the space of mainstream national media, that of the social networking sites and the intellectual discourse. For each narrative, "symptoms" and lines of development are discussed, in the frame of a critique of the hegemonic reading of the Covid-19 crisis. The text concludes by dwelling on the actions of deconstruction (of dominant narratives) and reconstruction (of marginalized narratives, as well as the scientific knowledge that can support them) as necessary areas of action for the sociology of communication in the context of the crisis.